Cough and asthma. - Pavord, I (2004)
Cough variant asthma and the closely related corticosteroid responsive cough syndromes eosinophilic bronchitis and atopic cough are common causes of chronic cough. The diagnosis is often not overt but detailed investigation of airway responsiveness and airway inflammation can be helpful. Cough variant asthma, eosinophilic bronchitis and atopic cough are all associated with eosinophilic airway inflammation, which is similar to that seen in non-cough predominant asthma. However, evidence of activated mast cells and increased concentrations of mast cell products appears to be confined to the conditions associated with cough, suggesting a role for mast cell degranulation in the superficial airway structures in the pathogenesis of cough. Cough variant asthma is typically corticosteroid responsive; leukotriene antagonists and antihistamines also help. Further study of this interesting asthma variant may increase our understanding of the relationship between airway inflammation and airway dysfunction.